PARLIAMENTARY ELECTIONS IN NAGORNO-KARABAKH: LEGAL AND POLITICAL ASPECTS - BABAIAN, David (CENTRAL ASIA AND THE CAUCASUS, 2005)
throughout the first half of 2005 parliamentary elections scheduled for 19 June remained topic No. 1 in Nagorny Karabakh, the electoral passions reaching their peak in May and June. This says that even though the Karabakh conflict has not yet been settled the people responded to the elections with the “fever” typical of peaceful times and much more stable situations.